ENERGIZING STUDENTS’ READING COMPREHENSION THROUGH MULTIMODAL TEXTS - Januarty, Resky -; Azizah Nima, Hanna Novariana (Universitas Negeri Makassar, 2018)
Teaching and learning process is an essential aspect of a successful English teaching and learning. Reading skill is one of the language skills in English which gives a huge input to the learner. Nevertheless, it is mostly found that reading material and its exercises examine explicitly of what have been learned. Recently, multimodal texts become more popular in educational aspect especially the use of multimodal text in the teaching and learning reading. Multimodal text is a text that contains semiotic mode which covers gesture, visual image, document, layout, music, architectural design, etc. This study interviewed 10 Junior High School students and 1 English teacher regarding the use of multimodal text in reading class. The design of the study was a qualitative descriptive study which investigates the use of multimodal texts in teaching learning process in Indonesia compare to other countries. This study is expected to have a deeper insight and significant contribution for the English pedagogy.